Teatro do oprimido: incorporações mediáticas de uma poética popular - Rodrigues, Anderson Zotesso (2010)
The present study brings to light the ramifications, incorporations and dialogues between radio and television elements in plays and/or sketches based upon the poetics of the Theater of the Oppressed as systematized by the dramatist Augusto Boal, paradigmatically, against the attempts of mediatic manipulations of individual behaviors and cultural practices. The purpose, specifically, is to demonstrate how, predominantly in popular theater stagings, ways to interpret, to narrate, certain gestures, themes and songs that are part of these two mediums of mass communication embedded in the urban home tend to appear as a part of the plays. The theoretical basis of this research lays in the elaborations by Jesus Martin-Barbero of the dialogues between mass media and culture, and in the relations between media, culture and economy as proposed by Néstor García Canclini. The bibliography by Augusto Boal as well as articles about his propositions also constitute an important part of the present study, since they serve as material for the poetical elaboration of the plays staged by the researched groups. To accomplish our field research, certain plays were elected as objects of study, such as Que onda con Borges? , staged by the Infierno de los vivos, a group from Buenos Aires, Argentina, and the play Um dia a casa cai , staged by GATO (Teenage group of theater of the oppressed), from São Paulo, Brazil. Interviews with members and analysis of the plays were conducted between July, 2008 and January, 2010. The present study also contains a critical analysis of the institutional, political and economical relations developed by organizations and theatrical groups of São Paulo and Londrina, in order to detail and interrelate the political and aesthetic options of such groups